Introduction of a Capillary Gel Electrophoresis-Based Workflow for Biotherapeutics Characterization: Size, Charge, and N-Glycosylation Variant Analysis of Bamlanivimab, an Anti-SARS-CoV-2 Product - Szabo, Miklos; Sarkozy, Daniel; Szigeti, Marton; Farsang, Robert; Kardos, Zsofia; Kozma, Adam; Csanky, Eszter; Chung, Doo Soo; Szekanecz, Zoltan; Guttman, Andras (Frontiers in Bioengineering and Biotechnology, 2022)
Coronavirus Disease 2019 (COVID-19) is a major public health problem worldwide with 5-10% hospitalization and 2-3% global mortality rates. The disease is caused by a betacoronavirus called Severe Acute Respiratory Syndrome Coronavirus 2 (SARS CoV-2). The receptor-binding domain (RBD) of the Spike protein expressed on the surface of the virus plays a key role in the viral entry into the host cell via the angiotensin-converting enzyme 2 receptor. Neutralizing monoclonal antibodies having the RBD as a target have the ability to inhibit ACE2 receptor binding, therefore, prevent SARS-CoV-2 infection, represent a promising pharmacological strategy. Bamlanivimab is the first anti-spike neutralizing monoclonal antibody, which got an emergency use authorization from the FDA for COVID-19 treatment. The effector function of antibody therapeutics is greatly affected by their N-linked carbohydrates at the conserved Fc region, influenced by the manufacturing process. Various capillary gel electrophoresis methods are widely accepted in the biopharmaceutical industry for the characterization of therapeutic antibodies. In this paper capillary SDS gel electrophoresis was used for size heterogeneity analysis to determine the presence/absence of the non-glycosylated heavy chain (NGHC) fragment. Capillary gel isoelectric focusing was used for possible N-glycosylation mediated charge heterogeneity determination, e.g., for excess sialylation. Finally, capillary gel electrophoresis was applied for N-glycosylation profiling and sequencing. Our results have shown the presence of negligible amount of non-glycosylated heavy chain (NGHC) while 25% acidic charge variants were detected. Comprehensive N-glycosylation characterization revealed the occurrence of approximately 8.2% core-fucosylated complex and 17% galactosylated N-linked oligosaccharides, suggesting the possible existence of ADCC effector function in addition to the generally considered neutralizing effect of the therapeutic antibody molecule.